Design and implementation of web product search engine (Part 1) - Lim, Geok Mui. (2011)
The purpose of the study is to develop a robust and well-designed Web Product Search Engine –Visual Image Search Engine (VISE), providing both text and image search functions. VISE is developed by a team of five students.